International criminal Responsibility for terrorist crimes - المالكي, هادي نعيم; عبد الكاظم, ميثم شاكر (Journal of Legal Sciences, 2019)
This research is entitled "International criminal Responsibility for terrorist crimes". Individuals bear the international criminal responsibility for supporting terrorist crimes, whatever their status, whether they are ordinary persons, heads of state or state officials. They could be prosecuting through national or international courts. Although terrorist crimes are not mentioned in the Statute of the International Criminal Court, terrorist groups may be prosecuting before the International Criminal Court when they commit international crimes within the jurisdiction under the Statute of this court, i.e., genocide, crimes against humanity or war crimes. Leaders and officials of States that support terrorism could be prosecuting also on the basis of the provisions of criminal contribution to the commission of international crimes within the jurisdiction of International Criminal Court.